2015
DOI: 10.1007/s00436-015-4399-x
|View full text |Cite
|
Sign up to set email alerts
|

Hymenolepis folkertsi n. sp. (Eucestoda: Hymenolepididae) in the oldfield mouse Peromyscus polionotus (Wagner) (Rodentia: Cricetidae: Neotominae) from the southeastern Nearctic with comments on tapeworm faunal diversity among deer mice

Abstract: A previously unrecognized species of hymenolepidid cestode attributable to Hymenolepis is described based on specimens in Peromyscus polionotus, oldfield mouse, from Georgia near the southeastern coast of continental North America. Specimens of Hymenolepis folkertsi n. sp. differ from those attributed to most other species in the genus by having testes arranged in a triangle and a scolex with a prominent rostrum-like protrusion. The newly recognized species is further distinguished by the relative position and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 48 publications
2
17
1
Order By: Relevance
“…In this study, the phylogenetic tree revealed that C. megalops is distantly related to the genus Hymenolepis , supporting the view of Makarikov et al [13] who preferred to retain the independent status of Cloacotaenia based on the morphological characteristics. The present results also suggest that Pseudanoplocephala crawfordi is a member of the genus Hymenolepis as shown in previous studies [10, 27].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the phylogenetic tree revealed that C. megalops is distantly related to the genus Hymenolepis , supporting the view of Makarikov et al [13] who preferred to retain the independent status of Cloacotaenia based on the morphological characteristics. The present results also suggest that Pseudanoplocephala crawfordi is a member of the genus Hymenolepis as shown in previous studies [10, 27].…”
Section: Resultssupporting
confidence: 87%
“…Czaplinski & Vaucher [12] considered Cloacotaenia a synonym of Hymenolepis but Makarikov et al [13] have recently restored the independent status of the genus Cloacotaenia based on remarkable morphological differences between C. megalops and Hymenolepis ( sensu stricto ). To tackle these issues, in the present study, the complete mt genome of C. megalops was determined and its phylogenetic relationships with selected cestode species were inferred based on analysis of the concatenated mt amino acid sequences.…”
Section: Introductionmentioning
confidence: 99%
“…An increasingly comprehensive understanding of diversity among rodent helminth faunas remains confounded by poor availability of voucher specimens linked to a diverse series of surveys over the past century (Makarikov et al 2015). For example, considering the species-rich genus Peromyscus Gloger, (Cricetidae, Neotominae), representative series of voucher specimens of hymenolepidid cestodes and other helminths were only sporadically deposited following many local to regional surveys across North America (e.g., Erickson 1938; Hansen 1950; Grundmann and Frandsen 1960; Babero and Matthias 1967; Vaughn 2013).…”
mentioning
confidence: 99%
“…Further, many studies provided only incomplete identification to the generic level, leaving substantial gaps in our documentation of the fauna. Consequently, new field collections that provide access to comparative materials for integrated morphological/molecular analyses are essential to enhance our ability to more completely document parasite faunal diversity among Nearctic rodents (e.g., Haukisalmi et al 2010; Hoberg et al 2012; Gardner et al 2014; Makarikov et al 2012, 2013, 2015). Archival deposition of georeferenced specimens from inventory remains a basic foundation for characterization of faunal structure (e.g., Hoberg et al 2009) and is increasingly necessary given the expanding recognition of cryptic diversity across many groups of parasites and hosts (Pérez-Ponce de León and Nadler 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation